Total Percutaneous Cardiopulmonary Bypass for Robotic and Endoscopic Atrioventricular Valve Surgery. Issue 4 (July 2017) - van der Merwe, Johan; Casselman, Filip; Beelen, Roel; Van Praet, Frank
Continuous technological advances in endoscopic-, robotic-and catheter-based cardiac interventions are paralleled by rapid evolution in cannulation strategies for circulatory support. The recent introduction of suture-based percutaneous vascular closure devices resulted in innovative strategies to deliver peripheral endovascular therapeutic devices through the iliac and femoral arteries. Percutaneous access allows rapid postoperative mobilization and potentially avoids the devastating neurolympho-vascular- and wound infection morbidities associated with conventional open surgical exposure. We routinely perform endoscopic port access surgery for all isolated atrioventricular valve pathology and extended the application of suture-based percutaneous vascular closure device to establish total percutaneous peripheral cardiopulmonary bypass in disabled, immune-suppressed, and morbidly obese patients at risk neuro-lympho-vascular- and wound infection. In this report, we provide a stepwise description of our total percutaneous peripheral cardiopulmonary bypass technique.